Comparison of hybrid models in temperature prediction in the Libyan city of Sirt - Muhammad Baay Mohammed, Abdslam K. Suliman and Nuri Omer. Ali (Journal of Pure & Applied Sciences, 2019)
Temperature forecasting is one of the most important factors in climate studies such as agriculture, vegetation, water resources and tourism. Given the importance of temperature forecasting we believe that there is a real need to develop appropriate solutions for reading the future in terms of accuracy, quality and reliability. This paper compares several advance methods of prediction; including (EMD/EEMD/SEMD) with ARIMA model using temperature recorded data in the Libyan city of Sirte from 1945 to 2010. Predicting the next 10 years tells us that the best of these methods is (SEMD with ARIMA model).